Effectiveness of various leg muscle training methods on increasing leg muscle strength - M. Frans Surya Pradana; Setiorini, Anggi; Agustina Daulay, Suryani; Ismunandar, Helmi (Universitas Negeri Yogyakarta, 2025)
Lower limb muscle strength is crucial for functional human activities, providing body stabilization, maintaining posture, and enabling various movements. Insufficient training can hinder muscle protein synthesis, leading to diminished strength in the lower limbs. Regular training, particularly resistance exercises, is essential for improving this strength. Numerous training methods have been developed, such as resistance training, plyometric exercises, bodyweight exercises, isolation training, movement-based practices, and technology-assisted techniques, though their relative effectiveness remains a topic of ongoing evaluation. This literature review aims to assess the effectiveness of various lower limb strength training methods across diverse populations, including adolescents, athletes, and older adults. The review involved a systematic search of PubMed and Google Scholar, using defined inclusion and exclusion criteria, resulting in 16 eligible studies. The effectiveness of each training method was analyzed by comparing study findings, which incorporated different research designs. All included studies indicated significant improvements in lower limb strength, although the magnitude of the improvements varied based on training intensity, duration, and participant characteristics. Compound and resistance training demonstrated comprehensive strength gains, plyometric exercises improved explosive power, and isolation training was particularly effective for strengthening specific muscle groups. Among older adults, combined training proved to be the most effective, enhancing both strength and balance, as well as functional mobility. These results highlight that no single training method is universally superior, underscoring the importance of customizing exercise programs to meet individual needs and objectives.